Identification of Determinants of Participation in Esports Games and Quality Assessment of Live Game Streaming Services - A Research Proposal - Marcin SZOSTAKOWSKI; Jacek WINIARSKI (Communications of International Proceedings, 2021)
The purpose of this paper is to present a research proposal on the phenomenon of popularity of esports games among Internet users. The text describes the research project, which is to cover two problem areas. The first area is to identify the determinants of motivation to participate in esports services, while the second is to assess the quality of live game streaming services offered by the most popular Twitch service. The article describes the phenomenon of esports, discusses the principles of the selection of research tool (authors’ modification of E-SERVQUAL method), and presents the details of the planned diagnostic survey that will be carried out through the survey questionnaire presented in the text. The article ends with a description of the planned research schedule.
Keywords: Esports; E-SERVQUAL; Live Game Streaming Services